The Impact Of Online Loans on Consumptive Behavior Among Students In The City Of Bandung - Novik Andriana; Elly Malihah; Siti Nurbayani (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2023)
This research aims to analyze the impact of online loans on the consumptive behavior of students in the city of Bandung. Online loans have become a significant phenomenon in today's modern society, especially among students vulnerable to the influence of the digital economy. The method used in this research is qualitative descriptive. The data collection techniques used were observation and in-depth interviews. There were 12 informants in this study, consisting of 10 key informants who are students and two supporting informants. The research was conducted at the UPI Setiabudhi campus and Pasundan University in the city of Bandung. The theoretical analysis uses Ulrich Beck's concept of the risk society to analyze changes in modern society that are increasingly filled with complex risks in the context of online loans and the consumptive behavior of students. The results of this research indicate that online loans significantly impact students' consumptive behavior. Factors such as ease of access, product promotions, and social pressure encourage students to take online loans, thereby influencing their consumptive habits. Based on the research results, students in Bandung use the money from online loans for consumptive and hedonistic needs and lifestyles, such as hanging out, indulging, vacations, attending concerts, nightlife entertainment (clubbing), buying electronic goods, and showcasing possessions on social media.